A feasibility study of the toxic responses of human induced pluripotent stem cell-derived hepatocytes to phytochemicals. (October 2018) - Smutný, Tomáš; Harjumäki, Riina; Kanninen, Liisa; Yliperttula, Marjo; Pávek, Petr; Lou, Yan-Ru
Abstract: Herbal medicines have been increasingly used in the last three decades. Despite their popularity, safety issues with herbal products need to be addressed. We performed a feasibility study of the toxic responses of human induced pluripotent stem cell-derived hepatocytes (iHep cells) to phytochemicals in comparison with hepatoblasoma-derived HepG2 cells and long-term human hepatocytes (LTHHs). The iHep cells expressed typical hepatocyte markers cytochrome P450 3A4 (CYP3A4), hepatocyte nuclear factor 4α, and albumin despite the expression of immature markers α-fetoprotein and cytokeratin 19. We studied the responses of iHep cells to phytochemicals saikosaponin D, triptolide, deoxycalyciphylline B, and monocrotaline with different mode of toxicity employing MTS and lactate dehydrogenase (LDH) assays. Saikosaponin D and triptolide caused dose-dependent cytotoxicity in the iHep cells, which were more sensitive than LTHHs and HepG2 cells. Saikosaponin D-induced cytotoxicity tightly correlated with increased LDH leakage in the iHep cells. Although deoxycalyciphylline B did not exhibit toxic effect on the iHep and HepG2 cells when compared with LTHHs, it decreased CYP3A7 expression in the iHep cells and increased CYP1A2 expression in HepG2 cells. We hereby show the feasibility of using iHep cells to detect toxic effects of phytochemicals. Graphical abstract: Highlights: Study of toxic responses of human iPSC-derived hepatocytes (iHep) to phytochemicals. iHep expressed both adult and fetal hepatocyte markers. iHep revealed better prediction for some toxic phytochemicals than HepG2 cells.